Effects of moisture dehumidification on the performance and degradation of a proton exchange membrane fuel cell. (15th April 2022) - Xiao, Biao; Zhao, Junjie; Fan, Lixin; Liu, Yang; Chan, Siew Hwa; Tu, Zhengkai
Abstract: During the proton exchange membrane fuel cell (PEMFC) operation, liquid water accumulates in the PEMFC, causing water flooding and performance degradation, especially at high current densities. Moisture dehumidification has been used to remove excess water in PEMFCs by forming a high water vapor concentration gradient between the inside and outlet of PEMFCs. In this study, the cathode outlet gas was condensed by adding thermoelectric refrigeration equipment to the cathode outlet of a single cell, and the influence of gas condensation on PEMFC performance under different working conditions was studied. The results showed that the effect of moisture dehumidification on PEMFC performance depended on the water content in the PEMFC, and the positive effect was more evident under high current density, high relative humidity, and high pressure. Moreover, moisture dehumidification is beneficial to alleviate the degradation of the catalyst layer. When there was no exhaust gas condensation, large-area fractures and loss occurred in the catalyst layer after 100 h of operation, and the electrochemically active area (ECSA) was reduced by 22.28%. There was only a slight reduction in the thickness of the catalyst layer with moisture dehumidification, and the ECSA was only reduced by 1.82%. Therefore, the degree of moisture dehumidification should be adjusted according to the water content inside the PEMFC in actual operation. Highlights: The effects of moisture dehumidification on the PEMFC performance is studied. The effect of moisture dehumidification depended on the water content. Moisture dehumidification can effectively alleviate water flooding. The more water content in the PEMFC, the more obvious the positive effect. The degree of moisture dehumidification should be adjusted according to the water content.